2017
DOI: 10.1016/j.jveb.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between stepping and kicking behavior and milking management in dairy cattle herds

Abstract: Keywords: dairy cows behavior type of milking parlor stepping kicking milk production a b s t r a c t We studied the relationship between behavior during milking with milking parlor management, measuring the occurrence of steps and kicks, and cow-related factors. We also investigated the link between stepping and kicking during milking and udder health. A total of 2,903 direct observations of milking behavior were collected in 44 dairy herds in the north of Portugal. The results showed great variability in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
4
7
0
Order By: Relevance
“…Compelling evidence (P < 0.001) indicates that the switchpoint setting of 0.840 kg/ml specified the least proportion of kicking and stepping, teat base swelling, and rings post milking (Table 1). This agreed with Cerqueira et al (2017), establishing that overmilking led to significantly more stepping and kicking behaviour during milking. More cows had somatic cell counts exceeding 200 000 cells/ml of milk at this setting.…”
Section: Cow Comfort During Milkingsupporting
confidence: 79%
See 1 more Smart Citation
“…Compelling evidence (P < 0.001) indicates that the switchpoint setting of 0.840 kg/ml specified the least proportion of kicking and stepping, teat base swelling, and rings post milking (Table 1). This agreed with Cerqueira et al (2017), establishing that overmilking led to significantly more stepping and kicking behaviour during milking. More cows had somatic cell counts exceeding 200 000 cells/ml of milk at this setting.…”
Section: Cow Comfort During Milkingsupporting
confidence: 79%
“…This agreed with Cerqueira et al . (2017), establishing that overmilking led to significantly more stepping and kicking behaviour during milking. More cows had somatic cell counts exceeding 200 000 cells/ml of milk at this setting.…”
Section: Resultsmentioning
confidence: 98%
“…Multiparous cows seem to kick less (Cerqueira et al, 2017) and step more (Gygax et al, 2008;Cerqueira et al, 2017) than primiparous cows; however, Rousing et al (2004) observed that high-yielding cows older than parity 4 stepped less than did younger cows. Cows with an SCC >200,000 cells/mL (Gygax et al, 2008;Cerqueira et al, 2017) or with teat lesions (Rousing et al, 2004) were also found to kick more during milking. To limit the occurrence of these behaviors, they should first be detected objectively and easily.…”
mentioning
confidence: 93%
“…Stepping, flinching, footlifting, and kicking behaviors during milking occur for multiple reasons, such as deficiencies in the milking machine or husbandry conditions in the milking parlor (e.g., aversion to the human handler; Rushen et al, 1999;Rousing et al, 2004). In general, tech-nical deficiencies of the milking machine, such as over-milking (Cerqueira et al, 2017), high system vacuum levels, vacuum drops at the teat end (Besier et al, 2016), or high vacuum level in the mouthpiece chamber of the liner (Newman et al, 1991;Penry et al, 2017), have a detrimental effect on the teat (congestion, ringing at the teat base, lesions) and udder tissue conditions, which can lead to pain as well as defensive reactions and restlessness in cows. Intrinsic cow factors, such as parity or udder health, can also have an influence.…”
mentioning
confidence: 99%
“…It is of particular interest to assess the temperament of dairy cattle breeds known for expressing a more reactive temperament, reacting more intensely and with greater agitation to the handling procedures [ 18 ]. Among them, we highlight the dairy Gyr cattle [ 19 ], which are widely used for crossbreeding in tropical countries, like Brazil, where around 80% of the dairy herd are Holstein-Gyr crossbred cows [ 20 ].…”
Section: Introductionmentioning
confidence: 99%